Reputational Signaling through Sustainability Disclosure and Profitability in Stakeholder-Driven Markets - Hamrianto, Jeilan; Lasmaria S, Pingkan; Tansuria, Billy Ivan (Journal of Social Commerce, 2025)
This study examines the effect of corporate sustainability practices, as measured by GRI G4-based ESG disclosure scores, on stock prices in 38 mining companies listed on the Indonesia Stock Exchange during the period 2019–2023. In addition, corporate profitability (Return on Assets/ROA) is tested as a moderating variable to see whether the level of profit strengthens or weakens the relationship between ESG and stock prices. Panel data are analyzed using pooled OLS with robust standard errors after passing a series of classical assumption tests. The regression results show that neither ESG scores nor ESG×ROA interactions have a significant effect on stock returns, and the control variables also show no significance. The model only explains 3.50% of the variation in stock returns (R² = 0.0350), indicating that the dominance of other external factors such as commodity price volatility and macroeconomic policies have not been observed in this research model. This finding confirms that ESG sustainability signals have not been fully internalized by the capital market of mining companies in Indonesia, so that strengthening regulations, fiscal incentives, and independent audits are needed to improve the effectiveness of sustainability reporting.